Optimising Urban Public Health: Network-Driven Resource Allocation For Targeted Disease Control And Outbreak Prevention - M , Bhanurangarao; R, Dr. Mahaveerakannan (Migration Letters, 2023)
In densely populated urban areas, the swift propagation of infectious diseases presents formidable challenges in outbreak management and resource allocation. Traditional contact-tracing methods often falter amidst the intricate web of social connections within cities, resulting in delayed responses that exacerbate needless suffering, loss of life, and economic strain. This study proposes an innovative solution: resource allocation for network-driven disease control and outbreak prevention via targeted networks. By harnessing network analysis, this approach streamlines epidemic containment by directing resources precisely where they are most needed, thereby minimizing waste and optimizing resource utilization. Additionally, predictive modelling empowers pre-emptive measures to fortify resilience against future outbreaks. In essence, this research advocates for a proactive paradigm shift in urban public health, leveraging advanced analytics and strategic resource allocation to effectively combat infectious diseases while bolstering community preparedness.